EFEKTIVITAS KEGIATAN EKSTRAKURIKULER MENTORING AGAMA ISLAM DALAM PEMBENTUKAN AKHLAK - Saiful Akhyar Lubis; Neliwati Neliwati; Rahmawati Rahmawati (JP : JURNAL PENDIDIKAN, 2021)
Abstract: The article describes the effectiveness of Islamic mentoring extracurricular activities in moral development, where this research was conducted qualitatively at SMA Negeri 12 Medan, by observing the learning process of several informants for three mon-ths. The results of this study are that the first extra-curricular activities of Islamic Mentoring in moral development in schools have not been effective, this is due to the intrinsic factor of educators who have not been maximized due to limited human resources, se-condly because Islamic Mentoring extracurricular activi-ties are still relatively new so that further evaluation is needed to be developed, In addition to these intrinsic factors, there are other obstacles faced, namely the religious back-ground of students is very diverse so that not all Muslims have the awareness to participate. Third, Islamic mentoring extracurricular activities have not been fully supported by all school residents. The recommendation from the results of the study is that researchers in extracurricular or intra-curricular acti-vities should get special attention from all school members so that the formation of students' morals can be well directed.Keywords: extracurricular, leraning process, moral development